Seleksi Penerima Bantuan Pangan Istimewa Menggunakan Metode Simple Multi Attribute Rating Technique - Gellysa Urva; Welly Desriyati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
BPI  is a routine program distributed by PT Amandika Permana once a year to workers with criteria determined by the company. The increasing number of workers makes it difficult for companies to select workers who are eligible for food assistance. In order for the distribution of food aid to be channeled on target, the company needs an analysis and quick calculations in the selection process. The implementation of the SMART (Simple Multi Attribute Rating Technique) method with a large number of criteria is able to solve existing problems. The implementation of the SMART method is determined by applying ten criteria in the form of employment status, income, number of dependents, home ownership status, residential land status, building area, movable assets, sources of drinking water, sources of house lighting and other assistance program cards. The final results of the study show that the use of the SMART method is able to assist users in determining BPI beneficiaries. The decision results are divided into three categories, where values 0.5 – 0.8 are recommended, 0.3 – 0.4 are considered, and values 0.1 – 0.2 are not recommended. Attachments to the selected data make it easy for users to make decisions efficiently and effectively. Based on the results obtained, the beneficiary who is most entitled to assistance also occupies the first position with a value of 0.75. Determining the appropriate weight value for each criterion affects the selection results to get the best results.